SISTEM INFORMASI ANTRIAN LOKET PELAYANAN PT. POS INDONESIA CABANG BONDOWOSO BERBASIS WEB - Mutmainnah Ilmiatul Faidah; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
This research focuses on the development of a web-based information system designed to manage queues at the service counter of the PT Pos Indonesia Bondowoso Branch. It addresses common issues such as customer confusion, delays in service processes, and potential queue violations through an innovative digital solution. The system was implemented using a Waterfall model approach within the System Development Life Cycle (SDLC) framework and features automatic queue number retrieval, digital calling, live queue status updates, as well as daily and monthly queue recording functionalities.Employing technologies such as PHP, MySQL, and XAMPP, along with an interface designed in Adobe XD, this system provides a user-friendly and integrated solution. The implementation results demonstrate enhanced operational efficiency, streamlined processes, and reduced customer wait times. Overall, this system positively impacts counter services and facilitates better evaluation of service management. at the post office.